2015
DOI: 10.1016/j.bbagrm.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A liaison between mTOR signaling, ribosome biogenesis and cancer

Abstract: The ability to translate genetic information into functional proteins is considered a landmark in evolution. Ribosomes have evolved to take on this responsibility and, although there are some differences in their molecular make-up, both prokaryotes and eukaryotes share a common structural architecture and similar underlying mechanisms of protein synthesis. Understanding ribosome function and biogenesis has been the focus of extensive research since the early days of their discovery. In the last decade however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 126 publications
(167 reference statements)
1
72
0
1
Order By: Relevance
“…Ribosome biogenesis necessitates a major commitment in terms of cellular energy consumption, involving transcription from all three eukaryotic RNA polymerases, the spatial and temporal action of more than 300 ribosome assembly factors, and several quality control checkpoints to ensure proper ribosome assembly (1). In fact, given the substantial amount of resources invested in making ribosomes, the past few years have seen a growing body of evidence linking ribosome biogenesis to nutrient, growth factor, and stress responses (2), thereby implicating the regulation of ribosome biogenesis in stem cell homeostasis (3,4) and cancer biology (5).…”
mentioning
confidence: 99%
“…Ribosome biogenesis necessitates a major commitment in terms of cellular energy consumption, involving transcription from all three eukaryotic RNA polymerases, the spatial and temporal action of more than 300 ribosome assembly factors, and several quality control checkpoints to ensure proper ribosome assembly (1). In fact, given the substantial amount of resources invested in making ribosomes, the past few years have seen a growing body of evidence linking ribosome biogenesis to nutrient, growth factor, and stress responses (2), thereby implicating the regulation of ribosome biogenesis in stem cell homeostasis (3,4) and cancer biology (5).…”
mentioning
confidence: 99%
“…In the lung tumor, many signaling pathways are activated, including MAPK, NF-κB, ERK, and p38 Yao et al, 2015;Yun et al, 2015). Gentilella et al (2015) demonstrated that ribosome biogenesis was associated with tumor development. The TGF-β signaling pathway plays an important role in tumorigenesis and contributes to the hallmarks of cancer (Herbertz et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The choice between cleavage at site A 2 or A 3 has been lately shown to play an important regulatory role in stress conditions, including limited availability of nutrients . Ribosome production is then arrested, mainly due to the multifaceted activity of mTOR (TORC1) kinase . While it has been known for a long time that mTOR downregulates Pol I transcription, a recent report demonstrated that it also controls rRNA synthesis at the post‐transcriptional level, by forcing a shift from a normal processing at site A 2 to an alternative pathway, including cleavage at site A 3 .…”
Section: A Comparison Between the Various Stages Of Pre‐rrna Processimentioning
confidence: 99%
“…There are several mechanisms that impact the rate of ribosome biosynthesis in response to extra‐ and intracellular stimuli, for example, signalling pathways that involve mammalian target of rapamycin (mTOR) and proto‐oncogenes p53 and c‐MYC. Activity of these factors may either stimulate or suppress Pol I‐mediated rDNA transcription, as well as affect ribosome biogenesis at the post‐transcriptional level in response to changing environmental conditions or – like in the case of proto‐oncogenes – increase production of ribosomes in fast‐growing and proliferating cancer cells .These observations add an additional layer of complexity to the regulatory networks of ribosome biogenesis. Moreover, defects in ribosome assembly and composition have recently emerged as an important cause of several disorders, which, despite highly variable clinical manifestations, were classified together as one group of diseases, named ribosomopathies .…”
mentioning
confidence: 99%